The Youthful Nation and the Digital Ceiling: Examining the Paradox of EdTech Adoption amidst Systemic Capacity Gaps in Ethiopia - Belay Sitotaw Goshu; Muhammad Ridwan (Budapest International Research and Critics University, 2026)
Ethiopia's demographic surge, with 70% of its 135.5 million citizens under the age of 30, creates unprecedented pressure on an education system already grappling with profound learning poverty and infrastructure deficits. This paper examines the paradox of educational technology (EdTech) adoption amidst these systemic capacity gaps, introducing the